2013
DOI: 10.1371/journal.pone.0054012
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Men Who Have Sex with Men to Get Tested for HIV through the Internet and Mobile Phones: A Qualitative Study

Abstract: BackgroundMen who have sex with men (MSM) have the highest HIV prevalence in Peru, yet they are underserved by traditional preventive programs. In Peru, the Internet and mobile phones have emerged as an effective and convenient tool to reach this population.Methods and FindingsFrom October 2010 to February 2011, we conducted eight focus groups with gay identified MSM (closeted and out-of-the-closet) and with self-identified heterosexual MSM in order to identify key features and preferences to be used to tailor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Studies have shown that thorough explanation of the testing processes, the testing venue and knowing what needs to be done after the receipt of lab results increase the likelihood of undergoing a test, especially for stigmatized diseases [9]. If, on the contrary, patients believe that providers are withholding information, this can lead to mistrust, which can hamper the willingness to undergo tests and access care [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that thorough explanation of the testing processes, the testing venue and knowing what needs to be done after the receipt of lab results increase the likelihood of undergoing a test, especially for stigmatized diseases [9]. If, on the contrary, patients believe that providers are withholding information, this can lead to mistrust, which can hamper the willingness to undergo tests and access care [29].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of qualitative studies on diagnosis have focused on the health-seeking behavior of patients [5–9], but less so on the practicalities of the diagnostic system and the processes involved in reaching a diagnosis [10,11]. While some studies highlight different notions of risk, body, illness and healing that might influence decisions to seek a diagnosis [12], medical anthropologists such as Farmer [13] have emphasized that structural factors such as poverty and marginality determine care-seeking behavior and adherence to treatment or advice, rather than individual, rational decision making by patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study from Peru revealed that stigma reduction and increased HIV test uptake was associated with increased access to motivational messages that encouraged participants to overcome the fear of getting tested (Blas, Menacho, Alva, Cabello, & Orellana, 2013). In Nigeria, despite an entertainment-education intervention that changed some HIV stigmarelated attitudes and intentions to test for HIV, it was also noted that risk perceptions about HIV also mediated the relationship between both motivations to participate in the program and intentions to test (Lapinski & Nwulu, 2008).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…More than 20% of all new HIV infections in the US are among young people aged [13][14][15][16][17][18][19][20][21][22][23][24], and 92% of these new infections are diagnosed in YMSMmaking them one of the largest risk groups for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…However, formative research suggests that online, mobile, or social media outlets are acceptable and feasible means to increase uptake of prevention services and HIV testing among MSM. [16][17][18][19][20] Informed by extensive formative research, Dr. Patrick Sullivan of Emory University (one of iTech's Principal Investigators), with app developers from Keymind, developed and tested an HIV testing promotion app for adult MSM ("HealthMindr"). [21] Our initial formative research with YMSM [22] suggested interest in an HIV testing app like HealthMindr, but the youth agreed that it had to be adapted to be more culturally and developmentally appropriate for their peers.…”
Section: Introductionmentioning
confidence: 99%